1991
DOI: 10.18474/0749-8004-26.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Preference, Developmental Time, Adult Longevity and Fecundity of Green Peach Aphid (Homoptera: Aphididae) on Spinach

Abstract: Spinach, Spinacia oleracea L. breeding lines and a commercial cultivar were evaluated for differences in green peach aphid, Myzus persicae (Sulzer), preference, developmental time, adult longevity and fecundity. Aphid preference varied significantly among the breeding lines and the commercial cultivar ‘Kent.’ Line F70 was the only line significantly non-preferred when compared with ‘Kent’. Significant differences in aphid developmental time, adult longevity and fecundity were detected. Aphids held on line F70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the present study, the effect of cultivars on the prereproductive period was absent. In contrast, several works showed that this effect was present, for example, the green peach aphid Myzus persicae (Sulzer, 1776) on spinach, Spinacia oleracea L. (Mcleod et al, 1991), the cotton aphid, Aphis gossypii Glover, 1877on chrysanthemum and cucumber (Storer & van Emden, 1995;van Steenis & El-Khawass, 1995), the bird cherry-oat aphid Rhopalosiphum padi (Linnaeus, 1758) on wheat and triticale (Hesler & Tharp, 2005), the greenbug Schizaphis graminum (Rondani, 1852) on wheat (Castro et al, 2001), and the pea aphid Acyrthosiphon pisum on alfalfa, Medicago sativa (Golawska et al, 2008). Also, Guillaume & Boissot (2001) observed that the resistant cultivar of melon was prolonged the larval development of the melonworm Diaphania hyalinata (Linnaeus, 1767) to 17.08 days that the susceptible cultivar (12.57 days).…”
Section: Antibiosismentioning
confidence: 96%
“…In the present study, the effect of cultivars on the prereproductive period was absent. In contrast, several works showed that this effect was present, for example, the green peach aphid Myzus persicae (Sulzer, 1776) on spinach, Spinacia oleracea L. (Mcleod et al, 1991), the cotton aphid, Aphis gossypii Glover, 1877on chrysanthemum and cucumber (Storer & van Emden, 1995;van Steenis & El-Khawass, 1995), the bird cherry-oat aphid Rhopalosiphum padi (Linnaeus, 1758) on wheat and triticale (Hesler & Tharp, 2005), the greenbug Schizaphis graminum (Rondani, 1852) on wheat (Castro et al, 2001), and the pea aphid Acyrthosiphon pisum on alfalfa, Medicago sativa (Golawska et al, 2008). Also, Guillaume & Boissot (2001) observed that the resistant cultivar of melon was prolonged the larval development of the melonworm Diaphania hyalinata (Linnaeus, 1767) to 17.08 days that the susceptible cultivar (12.57 days).…”
Section: Antibiosismentioning
confidence: 96%